PROFITABILITAS, FIRM SIZE, LEVERAGE, DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE - Dimas Rizqi Dhaifullah (Jurnal Akuntansi dan Bisnis, 2025)
This study examines the influence of several internal company factors, such as profitability, leverage, company size, and audit committees, on tax avoidance practices in the banking sector listed on the Indonesia Stock Exchange (IDX) during the period 2018–2023. Tax avoidance is measured using the Effective Tax Rate (ETR) proxy. The method used is quantitative with a descriptive approach and employs multiple linear regression as the representative output of the analytical tool. The results of the study indicate that only Return on Equity (ROE) has a significant impact on tax avoidance, with a negative relationship meaning that the higher the ROE, the more aggressive the company tends to be in avoiding taxes. Meanwhile, the other variables do not have a significant impact.